Locally driven development: Overcoming the obstacles - and Ingram, George (Brookings Institution, 2022)
Locally led development is a complex process that the development community, in the U.S. and around the world, has spent several decades trying to get right. Yet, despite all the experience and lessons learned, it feels like we are barely beyond the starting line. This publication aims to contribute to the ongoing dialogue on locally led development, especially as to how the United States can address the obstacles posed by U.S. law, regulation, policy, and practice. It consists of two parts: An essay by George Ingram that notes the path that has taken us to this point, identifies key obstacles, and invites a discussion of how to overcome impediments and move forward. A set of 15 commentaries written by development experts that add a range of perspectives and nuances to the discussion